Sharing is living: The role of habitat heterogeneity in the coexistence of closely related species - Sanches, Fábio H. C. [UNESP]; De Grande, Fernando R. [UNESP]; Costa, Tânia M. [UNESP]; Barreto, Rodrigo E. [UNESP] (Wiley, 2023)
In biologically diverse ecosystems, an essential process to support competing species to coexist is ecological differentiation. Habitat heterogeneity is, hence, important in establishing species abundance and richness, favoring the coexistence of species due to habitat partition. In this context, shading and species thermal tolerance can be good factors to elucidate the role of habitat heterogeneity in the habitat partition among closely related species. Herein, we study shading effects in microhabitat selection, behavior, and physiological limitation on two species of fiddler crabs (Leptuca leptodactyla and Leptuca uruguayensis). Indeed, shading conditions influenced fiddler crabs species proportion over time, with L. leptodactyla more associated with nonshaded/warmer areas while the L. uruguayensis to shaded/cooler ones. They also adjusted their behavior differently from each other to deal with thermal stress. Finally, we have demonstrated that these effects are related to species' physiological limitations. We conclude that biologically diverse ecosystems, such as intertidal regions from estuaries (e.g., mudflats and mangroves), support the coexistence between closely related species by reducing competition due to habitat partition.
Keywords: behavioral ecology; fiddler crab; habitat partition; heat stress; spatial distribution; sunlight shading; thermoregulation